Will's visions of Piers Plowman, do-well, do-better, and do-best : a lemmatized analysis of the English vocabulary of the A, B, and C versions as presented in the Athlone editions, with supplementary concordances of the Latin and French macaronics - Wittig, Joseph S. (Langland, William, 1330?-1400? Piers Plowman (Three versions), 2001)
This is a complete Concordance to the A, B and C texts of Piers Plowman in the Athlone Press editions. Each word in the vocabulary of the three versions (approximately 5,400) is listed alphabetically in its order of occurrence within the particular version, in the succession A, B, C. Except for a few words of extremely frequent occurrence such as the definite and indefinite articles, common conjunctions and the personal pronouns (all these are indexed) each occurrence of each word is listed within its line of context. Words of similar spelling are, where called for, lexicographically distingui.